2009
DOI: 10.1002/chem.200900636
|View full text |Cite
|
Sign up to set email alerts
|

A Gadolinium‐Binding Cyclodecapeptide with a Large High‐Field Relaxivity Involving Second‐Sphere Water

Abstract: A new cyclodecapeptide incorporating two prolylglycine sequences as beta-turn inducers and bearing four side chains with acidic carboxyl groups for cation complexation has been prepared. Structural analysis in water by (1)H NMR spectroscopy and CD shows that this template adopts a conformation suitable for the complexation of lanthanide ions Ln(3+), with its carboxyl groups oriented on the same face of the peptide scaffold. Luminescence titrations show that mononuclear Ln-PA complexes are formed with apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 71 publications
2
65
1
Order By: Relevance
“…Because UO 2 2+ binding sites have barely been identified in proteins, we adopted a biomimetic approach using phosphorylated peptides that benefit from a preorganized backbone structure to mimic those binding sites in proteins. Previous studies from our group demonstrated that cyclic peptides with two Pro‐Gly β‐turn inducers can orient four coordinating amino acid side chains toward one face of the peptide (Scheme , left), as shown by structural solution NMR spectroscopy . These β‐sheet peptide structures could thus promote the coordination of the four side‐chains in positions 1, 3, 6, and 8 to the UO 2 2+ cation in the equatorial plane .…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Because UO 2 2+ binding sites have barely been identified in proteins, we adopted a biomimetic approach using phosphorylated peptides that benefit from a preorganized backbone structure to mimic those binding sites in proteins. Previous studies from our group demonstrated that cyclic peptides with two Pro‐Gly β‐turn inducers can orient four coordinating amino acid side chains toward one face of the peptide (Scheme , left), as shown by structural solution NMR spectroscopy . These β‐sheet peptide structures could thus promote the coordination of the four side‐chains in positions 1, 3, 6, and 8 to the UO 2 2+ cation in the equatorial plane .…”
Section: Introductionmentioning
confidence: 77%
“…Various structures have been exploited with several degrees of pre‐organization. The structures tested include simple linear sequences extracted from the protein structure, short peptides with hairpin turns, and cyclic peptides . Supramolecular peptide assemblies such as three‐stranded coiled coils have also been used to produce functional metalloenzymes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The translational self‐diffusion coefficient is an important parameter defining the outer‐sphere relaxivity, but it can also be related to the rotational correlation time (equation 4), through the rotational diffusion coefficient with the assumption that the translational and rotational microviscosity factors are equal 36. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Although the solution structure of the apopeptide highlights a conformation suitable for complexing Ln 3 + ions, with the four carboxyl side-chains oriented on the same face of the peptide scaffold, the stability of the lanthanide complexes is also in the micromolar range (log b pH 7 11 % 6.5). [11] The above-mentioned examples show that there is an intrinsic limitation in the stability of lanthanide-peptide complexes if only natural amino acids are used. Indeed, the latter bear only simple binding groups, like carboxylates (Asp, Glu), phenolates (Tyr), or amides (Asn, Gln, backbone peptide linkage), which have a low affinity for Ln 3 + in comparison with synthetic multidentate ligands of the poly-(aminocarboxylate) family.…”
mentioning
confidence: 96%